AB0572 Efficacy and safety of rituximab for anca associated vasculitis. (15th June 2017) - Fujita, K; Hirata, M; Oguni, S; Nakashima, Y; Nomura, Y; Yamamura, Y; Nonaka, K; Shibutou, N; Momoki, N; Ueno, A; Ombe, T; Maruyama, K; et al.
Abstract : Background: In Japan, rituximab (RTX) has become one of the dominant alternatives for ANCA associated vasculitis (AAV) even for elderly patients. Objectives: The efficacy and safety of RTX for AAV patients was determined at our hospital. Methods: Nineteen patients with AAV, including 14 newly diagnosed patients and 6 relapsed patients, had been treated with RTX. There were 10 males and 9 females. They were all MPO-ANCA positive; 16 were diagnosed with microscopic polyangiitis (MPA), 2 with granulomatosis with polyangiitis (GPA), and 1 with undifferentiated, according to the EMA classification of AAV. The mean age at RTX induction was 71.3 years (range: 40 – 82 years). The efficacy was evaluated by the BVAS score at the time of first induction and after 6 month treatment. Adverse events were recorded during the 6-month treatment. Results: The mean of BVAS decreased from 17.3 (range: 7–35) at the first induction to 1.2 (0–4) at 6 month of RTX treatment. Of the 10 patients who could be followed-up for over 6 months, 7 patients achieved remission (BVAS=0) (remission rate: 70.0%). The titer of mean MPO-ANCA decreased 136.1 IU/mL (9.9–300 IU/mL) to 44.4 IU/mL (1.0–114.0 IU/mL) at 6 month. The dose of prednisolone decreased from 34.4mg/day (5–60mg/day) at baseline to 5.5mg/day (0–10 mg/day) at 6 month. The adverse events were as follows: 3 patients experienced reactivation of cytomegalovirus (CMV) with a CMV colitis, one patient with sepsis following urinary-tract infection, and one patient with bacterial pneumonia. One patient with PMA died of exacerbation of the disease itself. Conclusions: In Japan, AAV, mostly MPO-ANCA-positive PMA, affects elderly persons. The results suggest that RTX may provide a therapeutic option for elderly patients at the age of over 70 years with severe MPA, with an acceptable safety profile and rapid glucocorticoid tapering. However, careful monitoring for infectious diseases will be needed. Disclosure of Interest: None declared